2010
DOI: 10.1364/boe.1.000059
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating atherosclerotic plaque burden in arterial tissues using femtosecond CARS-based multimodal nonlinear optical imaging

Abstract: A femtosecond CARS-based nonlinear optical microscope was used to simultaneously image extracellular structural proteins and lipid-rich structures within intact aortic tissue obtained from myocardial infarction-prone Watanabe heritable hyperlipidemic rabbits (WHHLMI). Clear differences in the NLO microscopic images were observed between healthy arterial tissue and regions dominated by atherosclerotic lesions. In the current ex-vivo study, we present a single parameter based on intensity changes derived from mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 46 publications
(36 reference statements)
1
41
0
Order By: Relevance
“…By probing the intrinsic vibrational signatures of carbonhydrogen (CH) bonds, CARS microscopy can easily detect CH-rich lipid structures in tissue. Consequently, CARS, in addition to other nonlinear microscopy techniques, has been applied to several studies on atherosclerosis, including the visualization of extracellular lipids and lipid-rich cells associated with plaque lesions ( 24,25 ) and the determination of lipid concentration levels in various lesions of the arterial intima ( 26,27 ). Previous work of our own utilized a multimodal CARS-based imaging technique to determine the impact of diet on macrophage infi ltration and lipid accumulation in early-stage atherosclerotic plaques ( 28 ).…”
mentioning
confidence: 99%
“…By probing the intrinsic vibrational signatures of carbonhydrogen (CH) bonds, CARS microscopy can easily detect CH-rich lipid structures in tissue. Consequently, CARS, in addition to other nonlinear microscopy techniques, has been applied to several studies on atherosclerosis, including the visualization of extracellular lipids and lipid-rich cells associated with plaque lesions ( 24,25 ) and the determination of lipid concentration levels in various lesions of the arterial intima ( 26,27 ). Previous work of our own utilized a multimodal CARS-based imaging technique to determine the impact of diet on macrophage infi ltration and lipid accumulation in early-stage atherosclerotic plaques ( 28 ).…”
mentioning
confidence: 99%
“…Recently arterial/atherosclerosis imaging was demonstrated by multimodal CARS-based microscopy. [1][2][3][4] These studies showed the power of label-free CARS imaging in differentiating plaques from healthy arterial surfaces as well as the potential of multimodal CARS to interrogate atherosclerotic plaque burden. In this study, multimodal femtosecond CARS was used for ex vivo epi-luminal imaging of extra-cellular proteins (elastic lamina and collagen fibrils) and lipid-rich structures (foam cells, extracellular lipid-deposit) within intact aortic tissue obtained from myocardial infarction-prone rabbits.…”
Section: Introductionmentioning
confidence: 87%
“…Strupler et al (2007Strupler et al ( , 2008 recently conducted two NLOM studies to investigate the three-dimensional heterogeneous accumulation of fibrillar collagen during fibrotic pathologies. In these works Strupler et al (2007) concluded that their protocol could be applied to analyze other types of diseased tissues, such as tissue from the cardiovascular system; however, according to Mostaço-Guidolin et al (2010), Strupler's protocol is not optimal to track extracellular changes associated with atherosclerotic lesion progression. Mostaço-Guidolin et al (2010) proposed a numerical optical index for determining plaque burden based on a linear combination of the three phenomenological scores originally proposed by Strupler et al (2007) which also included terms to account for the strong intercorrelation among major extracellular components during plaque progression.…”
Section: Quantitative Image Analysismentioning
confidence: 99%